Cinquain Poem: A Stimulating Instructional Media in Teaching Writing - Muhammad Fadhli; Sufiyandi Sufiyandi (Edukasi, 2020)
Writing, a skill that involved multiple facets of a language, is commonly considered to be the hardest skill to master. Using appropriate instructional media in teaching writing may make an enormous contribution to the achievement of students. This study explored the impact of cinquain poems as an instructional media on the ability of students to compose paragraphs by implementing a quasi-experimental research method. Sixty first semester students from English Education Study Program, Bengkulu University, chosen using total population sampling, were evenly divided into experimental and control groups. To assess their writing skills, the students were given a writing test as pre-test at the first meeting and a post-test at the sixteenth meeting. Inter-raters were used to eliminate bias in rating the work of students. The results of the paired sample t-test showed that implementing cinquain poems significantly improves the ability of students to compose paragraphs. In addition, independent sample t-test analysis also showed that the abilities of the students in paragraph writing were significantly higher than those who were not taught using cinquain poems. These findings indicate that it is beneficial to teach writing through cinquain poems to help students develop and organize their ideas, improve their vocabulary, and build an engaging learning atmosphere.